Systematic Analysis of NB-ARC Gene Family in Rice and Functional Characterization of GNP12 - Pan, Ying-Hua; Chen, Lei; Guo, Hai-Feng; Feng, Rui; Lou, Qi-Jin; Rashid, Muhammad Abdul Rehman; Zhu, Xiao-Yang; Qing, Dong-Jin; Liang, Hai-Fu; Gao, Li-Jun; Huang, Cheng-Cui; Zhao, Yan; et al. (Frontiers in Genetics, 2022)
The NB-ARC (nucleotide-binding adaptor shared by APAF-1, R proteins, and CED-4) gene family plays a critical role in plant development. However, our understanding of the mechanisms of how NB-ARC genes regulate plant development in the plant panicle is still limited. Here, we subjected 258 NB-ARC genes in rice to genome-wide analysis to characterize their structure, function, and expression patterns. The NB-ARC genes were classified into three major groups, and group II included nine subgroups. Evolutionary analysis of NB-ARC genes in a dicotyledon plant (Arabidopsis thaliana) and two monocotyledonous plants (Oryza sativa L. and Triticum aestivum) indicated that orthologous genome segments were conserved in monocotyledons and subjected to weak positive selective pressure during evolution. Dispersed and proximal replication events were detected. Expression analysis showed expression of most NB-ARC genes in roots, panicles, and leaves, and regulation at the panicle development stage in rice Ce253. The GNP12 gene encodes RGH1A protein, which regulates rice yield according to panicle length, grain number of panicle, and grain length, with eight major haplotypes. Most members of NB-ARC protein family are predicted to contain P-loop conserved domains and localize on the membrane. The results of this study will provide insight into the characteristics and evolution of NB-ARC family and suggest that GNP12 positively regulates panicle development.